2020
DOI: 10.1111/ijpo.12654
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' food parenting: A scoping review of the literature from 1990 to 2019

Abstract: Summary Background While food parenting is a robust area of inquiry, studies have largely focused on mothers. Given the diversity of family structures today and increases in fathers' engagement in caregiving, fathers' food parenting warrants attention. Objective We present a scoping review of research on fathers' food parenting (1990‐2019). Eligible studies included peer‐reviewed research published in English documenting fathers' food parenting and presenting results for fathers separate from mothers. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 94 publications
1
18
0
1
Order By: Relevance
“…However, in terms of the role that fathers played, results indicated that the Keeners who had a higher engagement of mothers had more overall changes at 4.5 months than the Uninvolved . In a recent scoping review, fathers are found to be involved in food parenting practices but not to the same extent as mothers and less so with day-to-day responsibilities ( Davison et al, 2020 ). The initial version of the Aim2Be app had a strong focus on supporting change in nutritional behavior, and it may be that this content is more relatable to mothers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in terms of the role that fathers played, results indicated that the Keeners who had a higher engagement of mothers had more overall changes at 4.5 months than the Uninvolved . In a recent scoping review, fathers are found to be involved in food parenting practices but not to the same extent as mothers and less so with day-to-day responsibilities ( Davison et al, 2020 ). The initial version of the Aim2Be app had a strong focus on supporting change in nutritional behavior, and it may be that this content is more relatable to mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The male-derived data included in the present review indicated that fathers played an assisting role during complementary feeding whilst allowing their female partners to lead in the decisionmaking process regarding timing of introduction and type of complementary foods. The quantitative literature that looked at both parents' feeding practices also suggests that mothers and fathers have distinct interaction with children regarding food with fathers being less likely to monitor children's food intake and apply restrictions on food compared with mothers (90) . In general, literature on fathers' feeding practices is limited and focuses primarily on childhood nutrition as opposed to infancy.…”
Section: Factors In Relation To Both Age Of Introduction and Type Of Solid Foodsmentioning
confidence: 99%
“…Others found that low family income was associated with poor fitness and high risk of obesity for children (40). Researchers examining barriers to physical activity in low-income communities in Colorado found the most commonly cited barriers were lack of low-cost options and traffic safety (41). We also found that daughter's sports participation and family income were significantly and positively correlated.…”
Section: Discussionmentioning
confidence: 48%